Islamic School Family Partnership in Strengthening Religious Learning Motivation - Ubaidillah; Puspa Pratiwi; Dwi Aida Masuhuma; Juleyah Fendi Dwi Rakhmawati; Natasya Putri Aulia (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This qualitative case study investigates how structured Islamic school–family partnerships strengthen religion-based learning motivation in a Madrasah Ibtidaiyah context. Drawing on Islamic educational philosophy and the School–Family Partnership framework, the study analyzes forms of parental involvement, implementation strategies, and their implications for students’ intrinsic religious motivation. Data were collected through interviews, participatory observation, and document analysis involving 10 teachers, 25 students, and 20 parents. Findings indicate that consistent religious routines at home, value-based role modeling, structured communication with teachers, and participation in school religious programs significantly reinforce students’ discipline, self-regulation, and engagement in Islamic learning. The study contributes theoretically by positioning religious motivation not merely as a behavioral outcome but as an integration of iman, akhlaq, and educational responsibility within a tawhidic framework. Practically, it proposes a context-sensitive model of Islamic school–family collaboration supported by digital communication and parenting modules to ensure sustainability. These findings provide implications for madrasah leadership in institutionalizing structured, value-based parental engagement to strengthen long-term religious learning motivation.